Comment on van Gemert et al. Asymptomatic Infant Rib Fractures Are Primarily Non-abuse-Related and Should Not Be Used to Assess Physical Child Abuse. Children 2023, 10, 1827 - Bernd Herrmann; Tanja Brüning; Sibylle Banaschak; Oliver Berthold (MDPI AG, 2024)
We are deeply concerned about the scientific quality of the article "Asymptomatic Infant Rib Fractures Are Primarily Non-abuse-Related and Should Not Be Used to Assess Physical Child Abuse" published in the journal Children in 2023 by van Gemert et al [...]